Microcredit Awarded To Women And Their Impact On Home Economics. - Murillo Limonez, Rosa Karina (2017)
Microcredit as a resource-generating tool contributes to improving the socio-economic situation of their families. Preferably, these are granted to groups of women of low and middle social strata. The objective is to receive financial microcredit for women entrepreneurs who need to improve their quality of life and reduce poverty in Quevedo. Surveys were applied to economically active women, with microenterprise activities. For the sample size, a population formula of less than 100,000 was used. The micro-entrepreneurial activity developed by women in Quevedo is identified by the commercialization of clothes with 30%, followed by the sale of food with 29.36%, shoe marketing, among the most important. In its daily commercial activity, 50.42% have received financing from private banks and 34.35% of women have obtained loans from the National Development Bank. 81.44% consider that the interest rate classification established by the Financial Institutions is acceptable. The financial resources obtained from microcredit are 65% that are earmarked for investment in the business, while 35% is used for overhead payments. For 66.48% of the women in Quevedo, microcredit had an impact on the improvement of quality of life, and 33.52 contributed to the reduction of poverty in each household of women entrepreneurs, promoting the socioeconomic development of the families of the canton